CONCENTRATION OF HEAVY METALS IN DRINKING WATER OF DIFFERENT LOCALITIES IN DISTRICT EAST KARACHI - JALEEL, MUHAMMAD ASIF; NOREEN, ROZINA; BASEER, ABDUL (Journal of Ayub Medical College Abbottabad, 2001)
Background: Several heavy metals are present in drinking water that play important roles in the body provided their level remains within the specified range recommended by WHO. But now due to the industriali7ation and rapid urbanization, the problems of pollution have surfaced. This study was designed to ascertain the contents of some heavy metals and then their variations if any in drinking water in different localities of district East of Karachi, Pakistan. Methods: Drinking water samples were collected from different sources and localities of district East of Karachi. The concentration of the heavy metals i.e. Lead, Arsenic. Copper, Iron. Mercury, Chromium, Manganese, Nickel, Cadmium and Zinc were determined by Atomic Absorption Spectrophotometry. Phi was estimated by pH meter. Total dissolved solids (TDS) were calculated by formula. These concentrations of heavy metals, pH and TDS were compared with the standards set by WHO. Results: Concentrations of lead and nickel were found to be significantly elevated as compared to WHO recommended levels in all the three sources of water (Piped water. Hand pump water and Tanker water supply). Chromium was found to be raised in hand pump water. Arsenic and Mercury were not detected in any source of water. Copper, iron, manganese, cadmium and zinc were found to be within the safe limits in all the three sources of water. pH was found to be within the range of WHO recommended level in all the three sources of water. TDS was found to be elevated in hand pump water and tanker water. Conclusion: Concentrations of lead and nickel were found to be significantly elevated as compared to WHO recommended levels in all the three sources of water in district East of Karachi.